Practicality Development Program for Mahendi Art Training for Empowering Women - Erifka Dwi Jayanti; Nizwardi Jalinus; Rahmiati Rahmiati (Postgraduate School, Universitas Negeri Padang, 2020)
The research objectives are: (1) developing a mahendi art training program for women's empowerment, (2) producing a mahendi art training program for practical women's empowerment. This study uses the ADDIE development model which consists of analysis, design, development, implementation and evaluation stages. The conclusions are: (1) Mahendi art training program has been successfully developed, (2) Mahendi art training program has been practically used for women's empowerment in the city of Medan.